Determination of the transcriptional regulatory region of a vaccinia virus late gene. - Weir, J P (1987)
A putative promoter region, extending from 218 base pairs (bp) before (-218) to 10 bp after (+10) the RNA start site of a vaccinia virus gene encoding an Mr-28,000 precursor of a core polypeptide that is expressed only after the onset of DNA replication was linked to DNA coding for the procaryotic enzyme chloramphenicol acetyltransferase (CAT). When this chimeric gene was inserted into the genome of vaccinia virus, the infectious recombinant expressed CAT in a regulated fashion. A series of deletions starting upstream of the promoter region and extending toward the RNA start site were made. The effects of these mutations on CAT expression were examined in cells infected with recombinant viruses and confirmed in a helper virus-dependent transient assay system. A gradual reduction in CAT expression occurred as the deletions extended from -61 to -18. Mutants that retained 18 bp before and 10 bp after the RNA start site still expressed CAT as a late gene product, although at a submaximal level. A further 5'-to-3' deletion of 10 bp reduced CAT expression to background levels. To demonstrate that the effect on expression was not simply due to the bringing of upstream inhibitory sequences closer to the RNA start site, a point mutation substituting a G for the A at -12 was made. The sharp decrease in CAT expression indicated the importance of a run of eight A residues located between -15 and -7. Evidence that these mutations affected the level but not the site of transcriptional initiation was demonstrated by analysis of the 5' ends of the mRNAs from infected cells. The short DNA sequence required for accurate and temporally regulated transcription suggests that the same or overlapping signals are used for both aspects of this process.